A new D‐galactose treatment monitoring index for PGM1‐CDG. Issue 5 (22nd June 2021) - Perales‐Clemente, Ester; Liedtke, Kristen; Studinski, April; Radenkovic, Silvia; Gavrilov, Dimitar; Oglesbee, Devin; Matern, Dietrich; Rinaldo, Piero; Tortorelli, Silvia; Morava, Eva; Raymond, Kimiyo
Abstract: Phosphoglucomutase 1 (PGM1) catalyzes the interconversion of glucose‐6‐phosphate to glucose‐1‐phosphate and is a key enzyme of glycolysis, glycogenesis, and glycogenolysis. PGM1 deficiency (OMIM: 614921) was initially defined as a glycogen storage disorder (type XIV), and later re‐classified as a PGM1‐congenital disorder of glycosylation (PGM1‐CDG). Serum transferrin (Tf) glycan isoform analysis by liquid chromatography‐mass spectrometry (LC‐MS) is used as a primary diagnostic screen tool, and reveals a very unique CDG profile described as a mixture of CDG‐type I and CDG‐type II patterns. Oral d ‐galactose supplementation shows significant clinical and metabolic improvements, which are indicated by the Tf glycan isoform normalization over time in patients with PGM1‐CDG. Thus, there is a need for biomarkers to guide d ‐galactose dosage in patients in order to maintain effective and safe drug levels. Here, we present a simplified algorithm called PGM1‐CDG Treatment Monitoring Index (PGM1‐TMI) for assessing the response of PGM1‐CDG patients to d ‐galactose supplementation. For our single‐center cohort of 16 PGM1‐CDG patients, the Tf glycan profile analysis provided the biochemical diagnosis in all of them. In addition, the PGM1‐TMI was reduced in PGM1‐CDG patients under d ‐galactose supplementation as compared with their corresponding values before treatment, indicating that glycosylation proceeds towards normalization. PGM1‐TMI allows tracking Tf glycan isoform normalization over time when the patients are on d ‐galactose supplementation.